Kebijakan Responsif Gender pada APBDes di Desa Cipayung Kecamatan Padarincang Kabupaten Serang Tahun 2020-2022: Gender Responsive Policy on APBDes in Cipayung Village, Padarincang District, Serang Regency 2020-2022 - Shifa Islaminur; Bayu Nurrohman (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2023)
The background of this research is the large number of women in village government in Cipayung Village, Padarincang District, Serang Regency, from village heads, village staff, heads of BPD, members of BPD, PKK, and posyandu. Researchers want to see how the policies made by the government of Cipayung Village are gender responsive or not. This study uses gender theory from Sara Longwe which has five indicators to analyze the level of equality and empowerment of women, namely welfare, access, awareness, participation and control. This research also uses qualitative methods and a case study approach in its writing. The results of this study are that Cipayung Village is not gender responsive in its APBDes, there is only a general budget for women, namely the PKK and Posyandu, there are no specific policies for women that can empower women. Even though there are many women who fill positions in village government, this does not mean that Cipayung Village has a special policy for women, this is because there is no initiative from the village head to make special policies for women starting from policies regarding welfare, access, awareness, participation, and control. As well as the absence of encouragement from women in Cipayung Village for the village government to make special policies for women that can empower women. There were deliberations on village development plans specifically for women in Cipayung Village, but women in Cipayung Village more often made suggestions related to physical development such as environmental roads and street lighting.